Service Design and Delivery How Design Thinking Can Innovate Business and Add Value to Society - Kurokawa, Toshiaki (Business Expert Press, 2015)
"There is absolutely no excuse not to have acquired more of your ideal business right after you've read this book." -Alan Weiss, PhD, author of Million Dollar Consulting and 55 other books. This book is designed to help organizations looking for significant growth. Offering a great product or service does not guarantee success-to win these days, a business must also excel at marketing and selling. In most instances, a big marketing team and budget also isn't necessary. To achieve big goals, focus must be put on the most important marketing and sales activities that generate the biggest impact for the business. This book outlines what those activities are and how to implement them
Description based on publisher supplied metadata and other sources
Keywords: Service industries--Management